Caesium fluoride-induced changes in the c.d. spectra of synthetic DNA fragments - Kypr, J; Vorlícková, M; Zon, G; Weiss, R; Arnold, L; Smrt, J (International journal of biological macromolecules, 1991)
Ten DNA fragments containing self-complementary alternating sequences of adenine and thymine differing in length and the starting nucleotide were studied by c.d. spectroscopy. It was found that d(TATATATA) but not d(ATATATAT), d(TATATA), d(CTATATAG) or (dT-dA)20 isomerized into the unusual X-DNA double helix at molar concentrations of CsF in solution. But in contrast to poly(dA-dT), the octamer (dT-dA)4, isomerized very slowly, at relatively low CsF concentrations and the isomerization was strongly dependent on the octamer concentration. A model is proposed to account for the observed properties of the B-to-X isomerization on the oligomer level.
Keywords: Molecular Sequence Data; konformace nukleové kyseliny; cesium; Models, Molecular; adeninnukleotidy; cirkulární dichroismus; Nucleic Acid Conformation; isomerie; DNA; Adenine Nucleotides; Spectrophotometry, Ultraviolet; Oligonucleotides; Base Sequence; sekvence nukleotidů; molekulární modely; Macromolecular Substances; Circular Dichroism; Fluorides; makromolekulární látky; thiminnukleotidy; Cesium; molekulární sekvence - údaje; spektrofotometrie ultrafialová; oligonukleotidy; Isomerism; polynukleotidy; Polynucleotides; fluoridy; Thymine Nucleotides